Tributação e orçamento público: um ensaio sobre o orçamento, a arrecadação tributária e o cumprimento de direitos do cidadão - Santos, Leonardo Sá dos (2022)
The main objective of this research is to understand whether it is possible that the current taxation and the budget can guarantee the rights of citizens provided for in the Federal Constitution of Brazil. To this end, this Dissertation assumes that the Constitution is a social contract established between the State and the Brazilian citizens to achieve the ambitious goal of the common good for all. The aforementioned rights materialize through the provision of public services by the State and this, in addition to organized state action, requires resources. In this sense, the Constitution established the collection of taxes as the main source of resources so that the State can face expenses related to its purposes. On the other hand, the planning of the public budget is an essential element in the structuring of public policies because it is through budget programming that it becomes possible to order expenses that aim at the protection of fundamental rights and guarantees. Therefore, there is no denying the interdependence between the budget and the taxation and both will be the object of the study throughout this work. In particular, the data related to the tax collection and the intrusion and the budget instruments defined in the Constitution are the Multiannual Plan (PPA), the Budget Guidelines Law (LDO) and the Annual Budget Law (LOA) in the last two cycles of the PPA. In continuity, as a guideline to assess whether the social contract is being fulfilled we analyze the opinions on the annual accountability of the President of the Republic, issued annually by the court of auditors of the Union (TCU) and, finally, the statistical analysis of the indicators Gross Domestic Product (GDP), GDP per capita and the Human Development Index (HDI).